2005
DOI: 10.1063/1.1835539
|View full text |Cite
|
Sign up to set email alerts
|

Growth and properties of AlGaInP resonant cavity light emitting diodes on Ge∕SiGe∕Si substrates

Abstract: Visible AlGaInP resonant cavity light emitting diodes (RCLEDs) were grown by molecular beam epitaxy and fabricated on low-dislocation density, SiGe∕Si metamorphic substrates. A comparison with identical devices grown on GaAs and Ge substrates shows that not only did the RCLED device structure successfully transfer to the SiGe∕Si substrate, but also a higher optical output power was obtained. This result is attributed to enhanced lateral current spreading by the low residual dislocation density (∼1×106cm−2) net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Very high Ge content SiGe virtual substrates (50%p[Ge]p70%) can serve as templates for the growth of compressively strained Ge (c-Ge)/t-Si dual channels [6][7][8], with impressive hole mobility enhancements (up to 10) over bulk Si [9,10]. SiGe virtual substrates graded all the way up to pure Ge (with therefore low threading dislocations densities (TDDs) [11,12]) enable the monolithic integration of high-performance III-V optical devices (such as p + /n GaAs solar cells [13], AlGaInP resonant cavity light emitting diodes [14], etc.) on large area Si substrates etc.…”
Section: Introductionmentioning
confidence: 99%
“…Very high Ge content SiGe virtual substrates (50%p[Ge]p70%) can serve as templates for the growth of compressively strained Ge (c-Ge)/t-Si dual channels [6][7][8], with impressive hole mobility enhancements (up to 10) over bulk Si [9,10]. SiGe virtual substrates graded all the way up to pure Ge (with therefore low threading dislocations densities (TDDs) [11,12]) enable the monolithic integration of high-performance III-V optical devices (such as p + /n GaAs solar cells [13], AlGaInP resonant cavity light emitting diodes [14], etc.) on large area Si substrates etc.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The materials engineering solutions to circumvent the lattice mismatch include metamorphic growth, 9,10 graded buffer layers, 11,12 selective epitaxial overgrowth, 13,14 and a variety of defect filtering strategies. [15][16][17][18][19][20] One of these engineering solutions is the use of virtual substrates, which consists of low-dislocation-density Ge grown on Si 12,21-23 and subsequently integrating III-V materials.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] One of these engineering solutions is the use of virtual substrates, which consists of low-dislocation-density Ge grown on Si 12,21-23 and subsequently integrating III-V materials. 9,24 Such engineering solutions may enable a variety of applications, including high-electron-mobility transistors (HEMTs) 10 integratable with the current Si complementary metal-oxidesemiconductor (CMOS) platform, light-weight, low-cost multijunction photovoltaics, [24][25][26] optical modulators, 27 and infrared detectors. [28][29][30] Despite the promising applications, two key engineering challenges exist for growing low-dislocation-density Ge on Si: lattice mismatch and thermal expansion coefficient (TEC) mismatch.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Furthermore, the equilibrium configuration serves as the starting point for kinetically-limited lattice relaxation calculations and is critical in determining the effective stress and therefore the driving force for dislocation flow. Several models have been developed for the determination of the equilibrium configuration [7][8][9][10][11][12][13][14][15] and, although it has been shown that the equilibrium configuration for a general semiconductor strained-layer structure may be determined numerically by energy minimization using an appropriate partitioning of the structure into sublayers, [7][8][9][10][11] such an approach uses specialized code, is computationally intense, and does not lend itself to an intuitive understanding necessary for innovative structure design.…”
Section: Introductionmentioning
confidence: 99%